2011
DOI: 10.1177/0300985811402843
|View full text |Cite
|
Sign up to set email alerts
|

Histologic, Immunohistochemical, and Clinical Features of 27 Mammary Tumors in 18 Male Dogs

Abstract: Twenty-seven mammary tumors from 18 male (3 intact, 15 neutered) dogs were collected. The average age at diagnosis was 9.2 years (range, 2-14 years). Seven of the dogs were Cocker Spaniels. Five dogs had multiple mammary tumors. All tumors were benign. Twenty-six were simple adenomas with mixed acinar and papillary patterns. The acinar pattern was predominant in 17 cases. One adenoma was complex with a prominent myoepithelial component. The myoepithelial component of 25 of the 25 tumors was immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…Of 226 mammary lesions in which the sex was known, only 1 adenocarcinoma occurred in a male. This is similar to feline 98 and canine 9 mammary tumors but contrasts with the situation in guinea pigs, in which a high proportion of mammary neoplasms occur in males. 3 Published reports 100 and our own data indicate that the condition of disseminated collagenous hamartomas (described in more detail below) occurs nearly exclusively in males (25/28 with known sex in our study).…”
mentioning
confidence: 50%
“…Of 226 mammary lesions in which the sex was known, only 1 adenocarcinoma occurred in a male. This is similar to feline 98 and canine 9 mammary tumors but contrasts with the situation in guinea pigs, in which a high proportion of mammary neoplasms occur in males. 3 Published reports 100 and our own data indicate that the condition of disseminated collagenous hamartomas (described in more detail below) occurs nearly exclusively in males (25/28 with known sex in our study).…”
mentioning
confidence: 50%
“…Adenoma was described in many cases, recorded depended upon metaplasia and dysplasia of epithelial cells into cuboidal to columnar with the presence of nucleus near the basement membrane (13).…”
Section: Discussionmentioning
confidence: 99%
“…The low occurrence of mammary neoplasms in male dogs corroborated previous studies that reported a frequency between 0 and 2. 7% (Brodey et al, 1983;Bearss et al, 2012). Some authors reported a lack of predisposition according to race (Peleteiro, 1994;Queiroga and Lopes, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries indicate that between 41 and 53% of mammary tumors are described as malignant (Brodey et al, 1983;Von Euler, 2011). However, in Brazil, the frequency of malignant neoplasms varies between 68 and 90% (Oliveira et al, 2010;Toríbio et al, 2012), which is similar to the prevalence observed in this study.…”
Section: Discussionmentioning
confidence: 99%